Democracy and Public-Private Partnerships in Global Governance
XV, 238 p.
Keywords: There has been rapid proliferation of public–private partnerships in areas of human rights, environmental protection and development in global governance. This book demonstrates how different forms of partnership legitimacy and accountability interact, and pinpoints trade-offs between democratic values in partnership operations.